Avaliação do H2O2 para a digestão de ingredientes farmacêuticos ativos da classe de anti-hipertensivos para a determinação de impurezas elementares por ICP-OES - Senger, Caroline Matte (2024)
In this work, a method for digesting an active pharmaceutical ingredient (API) sample was developed using microwave-assisted digestion (MAWD) in a high-pressure system in a single reaction chamber (SRC) using H2O2 as an oxidizing reagent. The SRC related parameters, such as temperature (190 to 250 °C) and sample mass (100 to 700 mg) were optimized in order to produce digests with lower residual C concentration. The optimal condition used 6 mL of 50% H2O2, digestion temperature of 250 °C and sample mass of 500 mg. The method, under this condition, was applied to the five studied samples of APIs (captopril, diltiazem hydrochloride, hydrochlorothiazide, enalapril maleate and methyldopa) and the residual carbon values in the digests were lower than 2400 mg L-1 and did not cause interference in the quantification of analytes by ICP-OES. Furthermore, the residual acidity was evaluated by determining pH and the results in the H2O2-MAWD-SRC digests obtained presented a pH in the range of 4 to 5, unlike the HNO3-MAWD-SRC method which presents a pH close to 0. The proposed method it was also evaluated with respect to accuracy, precision, specificity, robustness and quantification limit, and all of these figures of merit met the requirements of chapter 233 of the USP. The limits of quantification obtained by the proposed method comply with the limits of chapter 232 of USP and ICH. The green parameters of the method were evaluated by Eco Scale, resulting in a value of 83 considered “excellent”. The main advantage of using H2O2-MAWD-SRC is related to the fact that H2O2 produces only H2O and O2 as the major products of H2O2 degradation. Analysis of the mass spectra obtained for APIs, amino acids and their digests demonstrated the refractory characteristics of these compounds against wet digestion using H2O2. For all digests, the presence of APIs without being oxidized by H2O2 was identified, with the exception of HID. Despite the difficulty in interpreting the mass spectra of the digests, it can be seen that a large part of the oxidation reactions, involving the APIs, did not allow the complete oxidation of the aromatic structures present in these substances.